The costs and cost effectiveness of providing second-trimester medical and surgical safe abortion services in Western Cape Province, South Africa - Lince-Deroche, Naomi (PLoS One, 2018)
BACKGROUND: In South Africa, access to second-trimester abortion services, which are generally performed using medical induction with misoprostol alone, is challenging for many women. We aimed to estimate the costs and cost effectiveness of providing three safe second-trimester abortion services (dilation and evacuation (D&E)), medical induction with mifepristone and misoprostol (MI-combined), or medical induction with misoprostol alone (MI-misoprostol)) in Western Cape Province, South Africa to aid policymakers with planning for service provision in South Africa and similar settings. METHODS: We derived clinical outcomes data for this economic evaluation from two previously conducted clinical studies. In 2013–2014, we collected cost data from three public hospitals where the studies took place. We collected cost data from the health service perspective through micro-costing activities, including discussions with site staff. We used decision tree analysis to estimate average costs per patient interaction (e.g. first visit, procedure visit, etc.), the total average cost per procedure, and cost-effectiveness in terms of the cost per complete abortion. We discounted equipment costs at 3%, and present the results in 2015 US dollars. RESULTS: D&E services were the least costly and the most cost-effective at $91.17 per complete abortion. MI-combined was also less costly and more cost-effective (at $298.03 per complete abortion) than MI-misoprostol (at $375.31 per complete abortion), in part due to a shortened inpatient stay. However, an overlap in the plausible cost ranges for the two medical procedures suggests that the two may have equivalent costs in some circumstances. CONCLUSION: D&E was most cost-effective in this analysis. However, due to resistance from health care providers and other barriers, these services are not widely available and scale-up is challenging. Given South Africa’s reliance on medical induction, switching to the combined regimen could result in greater access to second-trimester services due to shorter inpatient stays without increasing costs.